Ḍā. Vāsireḍḍi Sītādēvi sāhityaṃ - Sītādēvi, Vāsireḍḍi (Viśālāndhra Pabliṣiṅg Haus)
Short stories and novels of an eminent Telugu authoress
Telugu in Telugu-Schr
Keywords: Telugu-Sprache; Erzählung; Geschichte 1900-2000; Roman